2012
DOI: 10.3928/01477447-20111122-14
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Train Patients to Limit Weight Bearing on a Lower Extremity?

Abstract: Orthopedic patients are often instructed on how much weight to bear on an injured or postoperative extremity. Although specific weight-bearing instructions are given to a majority of lower-extremity orthopedic patients, the ability of patients to comply with these instructions is questioned in the medical literature. This study compared the effectiveness of new forms of clinical interventions designed to train patients on weight bearing, focusing on the use of biofeedback devices designed to offer real-time fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 8 publications
1
62
0
Order By: Relevance
“…It should be kept in mind that another complicating factor could be lack of patient compliance with prescribed rehabilitation aftercare [14, 15]. A number of studies reported that patients often exceeded the prescribed level of partial weight bearing, even when self-reported compliance was high [16].…”
Section: Discussionmentioning
confidence: 99%
“…It should be kept in mind that another complicating factor could be lack of patient compliance with prescribed rehabilitation aftercare [14, 15]. A number of studies reported that patients often exceeded the prescribed level of partial weight bearing, even when self-reported compliance was high [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these concerns, the most notable issue with restricted weight bearing is poor patient compliance. Patients consistently exceed the allowed "weight" in partial weight bearing, despite believing they are compliant [33,36]. Other methods of retraining such as the use of a scale, tactile hand under foot, verbal cues, and auditory biofeedback have also failed to demonstrate efficacy [37,38].…”
Section: Restricted Weight Bearingmentioning
confidence: 99%
“…These devices use different technology to measure WB and to provide real-time feedback. Thereby, SmartStep has already been used in several studies on PWB [10,1416]. The recently developed OpenGo Science does not interfere with natural gait by using insoles without external modules attached to the body.…”
Section: Introductionmentioning
confidence: 99%